2012
DOI: 10.1007/s00339-012-6962-y
|View full text |Cite
|
Sign up to set email alerts
|

Red luminescence of Eu3+ doped ZnO nanoparticles fabricated by laser ablation in aqueous solution

Abstract: Fabrication of Eu 3+ -doped ZnO nanoparticles by laser ablation in liquid medium is reported. Sintered disks made of mixed powders of ZnO and Eu 2 O 3 are used for targets, and surfactant of sodium dodecyl sulfate or LiOH is included in solution. Round-shaped nanoparticles with the diameter of 5∼30 nm are synthesized. When the ZnO host is photoexcited, broad green photoluminescence (PL) of oxygen vacancies in the ZnO host as well as red PL of Eu 3+ is observed at room temperature. The red PL peak of Eu 3+ incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Ledoux et al confirmed the feasibility of preserving the phase (with some lattice disorders) and stoichiometry of the targets by transforming them into Y 2 O 3 :Eu 3+ , Lu 2 O 2 S:Eu 3+ , Gd 2 SiO 5 :Ce 3+ , Lu 3 TaO 7 :Gd 3+ , and Tb 3+ NPs with sizes as low as 5–10 nm using LAL . Other doped NMs have also been successfully produced, and researchers’ interest in doped NMs with upconversion properties is rapidly increasing. Overall, obtaining doped ternary or multinary oxides by LAL of doped solids is straightforward, and the colloids often exhibit related dopant functionalities (section ). However, more studies that focus on the selectivity of the synthesis related to a defined crystal phase, amorphous byproducts, or lattice defects are required.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ledoux et al confirmed the feasibility of preserving the phase (with some lattice disorders) and stoichiometry of the targets by transforming them into Y 2 O 3 :Eu 3+ , Lu 2 O 2 S:Eu 3+ , Gd 2 SiO 5 :Ce 3+ , Lu 3 TaO 7 :Gd 3+ , and Tb 3+ NPs with sizes as low as 5–10 nm using LAL . Other doped NMs have also been successfully produced, and researchers’ interest in doped NMs with upconversion properties is rapidly increasing. Overall, obtaining doped ternary or multinary oxides by LAL of doped solids is straightforward, and the colloids often exhibit related dopant functionalities (section ). However, more studies that focus on the selectivity of the synthesis related to a defined crystal phase, amorphous byproducts, or lattice defects are required.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…Doping (e.g., Eu 3+ ) introduction via LAL can not only render PL properties to intrinsically nonluminenscent biodegradable materials (e.g., hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 NPs), but also leads to superior bioimaging performance (e.g., blue, green, and red) of cells (Figure a–i) by varying the dopants (e.g., Tm 3+ , Tb 3+ , and Eu 3+ ) of magnetic Gd 2 O 3 colloids . When it comes to intrinsic luminescent particles, doping introduction often changes or paves a new radiative transition path between valence band and conduction band and results in an emission color change (e.g., blue emission and yellow emission of LAL-synthesized undoped and Mn-doped ZnS NPs, respectively) or color multiplexing (e.g., simultaneous blue/green emission of Cu-doped ZnS QDs, and green/red emission of Eu 3+ doped ZnO NPs). If the acceptor level is close to the valence band, significant PL emission enhancement is obtained with only a little shift of the PL peak; otherwise an apparent doping concentration-dependent PL shift is observed (e.g., Mg doped ZnO NPS) .…”
Section: Applicationsmentioning
confidence: 99%
“…of Ca, O, and Eu is rapidly cooled and nanoparticles including both Ca and Eu are expected to be produced with correct stoichiometry of the target. 18,[20][21][22][23][24] The photoluminescence from the Eu : HAp target and Eu : HAp nanoparticles synthesized by the LP-PLA technique using a laser fluence of 3.5 J cm À2 for 2 h is shown in Fig. 4(a).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the Mannich reaction route appears to be more facile because of the simple, low-temperature, and scalable process as well as its variety in selecting deposition substrates, which has never been reported in the previous growth. On the other hand, Eudoped metal-oxide-based materials such as TiO 2 , ZnO, and SnO 2 have been shown to be promising in sensors, transparent conductors, and optoelectronic devices [24][25][26]. It has been demonstrated that Eu-doped 1D nanocrystals may be used as a favorable energy transfer mediator capable of avoiding low absorption of optically center ions and photobleaching, which, in turn, could have a positive effect on photovoltaic devices [27].…”
Section: Introductionmentioning
confidence: 98%